2009
DOI: 10.1103/physreve.80.056404
|View full text |Cite
|
Sign up to set email alerts
|

Brownian dynamic of laser cooling and crystallization of electron-ion plasma

Abstract: Laser cooling and crystallization of electron-ion plasma is studied using the Brownian dynamics simulation technique and taking into consideration the interaction of ions with the electron subsystem. It has been shown that the nonlinear dependence of laser friction force on the velocity of ions has to be taken into account in order to simulate in an adequate manner the cooling dynamics and obtain a correct estimate for minimum temperatures. It has been found that times required for formation of an ordered ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…We see increasing coupling for ions with time, but it is limited by these heating effects. Attempts to access stronger Coulomb coupling, such as through proposed schemes to laser cool ions in UNPs 63,64,[88][89][90][91][92][93][94] or simply through plasma expansion as demonstrated here, should benefit from improved control of the initial density distribution of the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…We see increasing coupling for ions with time, but it is limited by these heating effects. Attempts to access stronger Coulomb coupling, such as through proposed schemes to laser cool ions in UNPs 63,64,[88][89][90][91][92][93][94] or simply through plasma expansion as demonstrated here, should benefit from improved control of the initial density distribution of the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…All the papers devoted to laser-cooled plasma [6][7][8][9] assumed that the laser radiation was shifted to the red range of the spectrum with respect to the electronic transition frequency of the ions. But what laser radiation spectrum is best for the purpose?…”
Section: Resonance Absorption Spectrum Of Ions In An Expanding Plmentioning
confidence: 99%
“…It was also shown that Wigner crystallization of the ion subsystem could be achieved in plasma. In [8] it was shown that the nonlinear dependence of the laser friction force on the ion velocity must be taken into account in order to simulate in an adequate manner the cooling dynamics and obtain a correct estimate for minimum temperatures. It has been found that the times required for formation of an ordered ionic structure can be much longer than the typical plasma cooling time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] and [5] a method of cooling ions was proposed aiming at obtaining non-ideal ionion interaction in electron-ion plasma. Later it was shown that the nonlinear dependence of laser friction force on the velocity of ions is an important consideration for laser cooling [6] and the spectrum of cooling laser radiation was described. [7] Photoionization of atoms induces ion-ion interaction resulting in correlation heating of ions.…”
Section: Introductionmentioning
confidence: 99%